Bhaymukt bugyal tatha anya kahaniya - Hatwal, Nand Kishore (Dehradun, Samaya Sakshaya, 2018)
Bhaymukt bugyal tratha anya kahaniya are the collection of ten stories by Nand Kishore Hatwal. Stories of the mountainous and social conditions of the mountain have been published in many reputable magazines. Through the stories of Nand Kishore Hatwal, the window of the life of the marginal mountain goes away.
Keywords: Fiction; Uttrakhand